Informing View of Organization - Travica, Bob (IGI Global, 2019)
Businesses are incorporating automated processes and information technology, as cost cutters or productivity boosters, into their business strategy now more than ever. However, as information systems (IS) research is further focusing on IS strategy, as well as advancing business strategy research, there is a need to examine the increasing integration of technology and automation through a clear framework. Informing View of Organization is such a framework. Informing View of Organization: Strategic Perspective features coverage on a wide range of topics such as group informatics, infoprocesses,